PERAN GANDA DAN KONTRIBUSI EKONOMI PEREMPUAN BURUH TANI HORTIKULTURA DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA - Sri Gintiyani; P. Setia Lenggono (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2021)
The results of research on women's involvement in supporting agricultural household economic activities in rural areas have encouraged women to perform multiple functions. This dual role is a quite complex problem for women. On the one hand, they have to carry out their functions as wives and mothers, on the other hand, women have to earn a living helping their husbands support the family economy. The objectives of this study were: (1) To describe the allocation of female working time as farm laborers and as housewives; (2) Describing the size of women's income contributions; and (3) Describe how big the family of women agricultural workers has achieved family welfare. The research location was chosen deliberately and using snowball techniques involving 30 respondents as farm laborers with the criteria coming from a complete family (having a husband and income). The main motivation of housewives in rural areas is to leave their domestic sphere, to work as horticultural farm laborers because their husband's income is still insufficient to meet family needs, so he follows the invitation of his colleagues to work. Part-time from their activities as agricultural laborers, the contribution to the total family income reaches 46 percent (not deducted from food allowance) and 45 percent (deducted by food allowance). The percentage of working time spent on productive activities is around 4.21 hours/day, while for reproductive activities it reaches 19.79 hours/day. Meanwhile, from the results of this study, it was also revealed that 78 percent of the families of female agricultural laborers were still in the underprivileged category.